THE EFFECT OF ADDING AQUADEST ON THE STABILITY OF HAIR SHINE SPRAY PREPARATIONS: A COMPARATIVE STUDY OF TWO FORMULAS - Dindy Sinta Megasari; Diva Nur Aini; Dien Haq Abdillah Mahakam (Universitas Negeri Surabaya, 2025)
Hair shine spray is generally based on non-aqueous solvents using volatile and non-volatile silicones. The addition of water (distilled water) to the system can affect the homogeneity and stability of the dispersion. This study aims to evaluate the effect of adding distilled water on the physical stability of hair shine spray by comparing two formulas: Formula A (containing distilled water) and Formula B (without distilled water). The experimental results showed that Formula A changed color to milky white when shaken and formed an unstable dispersion, while Formula B remained clear and stable without phase separation. These results indicate that the presence of water in the silicone–ethanol solvent system causes phase incompatibility which reduces physical stability. Keywords: Hair Shine, Silicon, Sunflower Oil.